The Arabic Word between phonology and Morphology - Raed Mohammad Mansoor (دراسات في اللغة العربيّة وآدابها)
The Arabic language tried to make harmony between the sounds making the word, which reflects easy pronunciation and apply less physical effort, and reaching a great way of clarity. The Arabic language also created its own phonological system and pattern that allows for easy articulation. This research paper tries to tackle one of the most important issues in Arabic phonology: i.e. the phonological and suprasegmental structure of the Arabic word. It shows that the making of Arabic word is done in accordance with the place of articulation as well as the manner of articulation, and allowing for segmental harmony, not difficult if articulated or heard. It also shows that the ease of articulation is considered a criterion for eloquence